Experimental investigation on surface behaviour of submerged arc welding fluxes using basic flux system. Issue 6 (15th April 2020) - Sharma, Lochan; Kumar, Jagdish; Chhibber, Rahul
Abstract: In present study, the wettability behaviour of basic submerged arc welding fluxes for the CaO–CaF2 –SiO2 & CaO–SiO2 –Al2 O3 welding flux system was studied by measuring the contact angle between the solid/liquid interfaces. Twenty-one submerged arc welding fluxes were formulated using mixture design approach. Contact angle of twenty-one basic fluxes were measured at 1100 °C at constant heating rate. X-ray fluorescence technique was used to evaluate the purity level of individual flux components. Phase analysis and structural properties of different fluxes were determined using Fourier transform infrared spectroscopy & X-ray diffraction technique. Using Young's & Boni's equations different surface tension values for CaO–CaF2 –SiO2 & CaO–SiO2 –Al2 O3 flux systems were determined from measured contact angle value. Dupre's equation was used to find the adhesion energy of the fluxes. Optimum wetting behaviour was observed for lower compositional range (i.e. for CaO/SiO2 & CaO/CaF2 ratio). Flux number 1, 2, 3, 4, 7, 12, 14, 17, 18, 19, 20 & 21 gives higher wettability and spreading area (mm 2 ) due to lower value of contact angle. With increase of CaO/SiO2 ratio there is significant increase in calculated surface tension.